Manajemen Adversity Quotient dalam Meningkatkan Kinerja dan Profesionalisme Guru di Kotabaru - Muhammad Muhaimin (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The increasing workload and pressure in the field of education necessitate effective Adversity Quotient (AQ) management to foster teacher resilience and uphold professionalism amid evolving challenges. This study aims to analyze how AQ management contributes to enhancing teacher performance and professionalism. In the face of continuous educational change, teachers are exposed to various pressures, including administrative burdens, curricular dynamics, and complex social expectations. AQ which consists of four core dimensions: Control, Ownership, Reach, and Endurance is considered a crucial factor influencing psychological resilience and professional consistency. This research employs a descriptive qualitative approach to explore managerial strategies, teacher perceptions, and experiences in developing AQ within the school environment. Data were collected through in-depth interviews, observations, and documentation. The findings reveal that AQ is managed through contextual and participatory approaches, supported by an open organizational culture, supportive leadership, and a psychosocially healthy work environment. Strengthening AQ has been shown to contribute to the development of adaptive, reflective, and professional educators. Therefore, integrating AQ into ongoing professional development programs is recommended as a strategic institutional response to the growing complexities of the educational landscape.